2017
DOI: 10.1007/s00726-017-2432-3
|View full text |Cite
|
Sign up to set email alerts
|

Human interstitial cellular model in therapeutics of heart valve calcification

Abstract: Calcific aortic valve disease is a common, severe heart condition that is currently with no proven, effective drug treatment and requires a surgical valve replacement or an entire heart explanation. Thus, developing novel, targeted therapeutic approaches becomes a major goal for cardiovascular disease research. To achieve this goal, isolated heart valve interstitial cells could be an advanced model to explore molecular mechanisms and measure drug efficacy. Based on this progress, molecular mechanisms that harb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 140 publications
0
7
0
Order By: Relevance
“…The expression of BMP2 has been shown to be mediated through NF‐κB signaling in order to induce valve calcification 75,76 . Since Selumetinib causes complete reversal of calcification, further investigation of the role of ERK signaling within the NF‐κB pathway to promote VIC calcification is warranted 62,77,78 . However, reduced RUNX2 gene expression suggests the potential involvement of the MAPK/ERK pathway in TNF‐α induced exacerbated calcification.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of BMP2 has been shown to be mediated through NF‐κB signaling in order to induce valve calcification 75,76 . Since Selumetinib causes complete reversal of calcification, further investigation of the role of ERK signaling within the NF‐κB pathway to promote VIC calcification is warranted 62,77,78 . However, reduced RUNX2 gene expression suggests the potential involvement of the MAPK/ERK pathway in TNF‐α induced exacerbated calcification.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, different animals were used to study disease pathologies due to the limitations of acquiring human samples. However, we now have the means to study calcification in AVS using human tissues [14,15,29], which according to our results, may be the only effective way to study the disease. Our study is limited, however, in that it only explores ALP-dependent calcification and does not address other molecular contributors including Runx2 [30], Wnts [4], UII [15], BMPs [31], and TGF-β [32].…”
Section: Discussionmentioning
confidence: 82%
“…We and others have shown that altered biomechanics can also promote calcific nodule formation when VICs are cultured on stiff matrices such as glass [ 24 , 88 , 89 ], or tissue culture polystyrene pre-coated with fibrin, laminin, and heparin also leads to an increase in the number of calcific nodules [ 90 ] or the addition of TGF-β [ 91 ]. In most assays, investigators utilize VICs isolated from human, porcine, and ovine models as these have been previously reported to have potential to undergo calcification in vitro (reviewed in [ 92 ]). Similar protocols for murine VICs have been more technically challenging, although intact, whole aortic valve explants can undergo osteogenic changes upon stimulation [ 93 , 94 ].…”
Section: Calcific Aortic Valve Diseasementioning
confidence: 99%